2021
DOI: 10.1080/01434632.2021.1922420
|View full text |Cite
|
Sign up to set email alerts
|

Extending the scope of the ‘cognitive advantage’ hypothesis: multilingual individuals show higher flexibility of goal adjustment

Abstract: The cognitive advantage (CA) hypothesis claims that multilingualism promotes the development of several basic cognitive capacities. A large number of empirical findings support this hypothesis, but recently there have also been numerous contradictory findings and methodological objections. The present paper extends the investigation of possible cognitive advantages from basic cognitive (executive) functions to broader cognitive competencies such as cognitive flexibility. A promising candidate for this is 'flex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 83 publications
2
5
0
Order By: Relevance
“…(1) Multilingualism may encompass (or be based on) a heterogeneous and diverse experience that stimulates the development of EC, especially ER. The current study extends earlier research going beyond accommodative coping (Greve et al, 2021;Koch et al, 2023) to emotional competence, including emotion regulation and its preconditions. A second path to a possible effect on EC is based on assumptions of the "narrow" cognitive advantage: (2a) Multilingualism may positively influence cognitive abilities, which are, in turn, (2b) necessary constituents of and/or helpful resources for emotional competences.…”
Section: A Two-path Framework For An Emotional Advantage Of Multiling...supporting
confidence: 77%
See 1 more Smart Citation
“…(1) Multilingualism may encompass (or be based on) a heterogeneous and diverse experience that stimulates the development of EC, especially ER. The current study extends earlier research going beyond accommodative coping (Greve et al, 2021;Koch et al, 2023) to emotional competence, including emotion regulation and its preconditions. A second path to a possible effect on EC is based on assumptions of the "narrow" cognitive advantage: (2a) Multilingualism may positively influence cognitive abilities, which are, in turn, (2b) necessary constituents of and/or helpful resources for emotional competences.…”
Section: A Two-path Framework For An Emotional Advantage Of Multiling...supporting
confidence: 77%
“…We, thus, assume that multilingualism might represent a diverse and heterogeneous life condition regarding linguistic, cultural, cognitive, and emotional dimensions that stimulate the development of different competences (Greve, 2023). So far, this assumption has only been tested with regard to accommodative coping (Greve et al, 2021). The goal of this paper is to test whether a similar effect can be found regarding another domain of regulatory competencesnamely, emotional competence.…”
Section: Extending the "Narrow" Cognitive Advantage Hypothesis: The H...mentioning
confidence: 91%
“…Thirdly, it should then be investigated in particular whether specific funding opportunities can be identified. For example, there is evidence that heterogeneous developmental conditions can be prognostically favorable for a more pronounced ability and willingness to make accommodative goal adjustments ( Greve and Thomsen, 2013 ; Thomsen and Greve, 2013 ; Greve et al, 2021 ; Koch et al, 2024 ). The promotion of accommodative skills and readiness in childhood has hardly been tested to date ( Greve et al, 2009 ); this would represent an important research desideratum.…”
Section: Discussionmentioning
confidence: 99%
“…There is some first evidence that heterogeneous life circumstances actually support (at least predict) individual adaptivity (here: individual preparedness and capability of goal accommodation). For instance, Greve and Thomsen (2013; found in two studies that heterogeneous leisure activities in childhood predict flexibility of goal adjustment in adolescence, and Greve et al (2021) found that multilingualism in childhood predicts flexibility of goal adjustment in adulthood.…”
Section: Adaptation: From Phylogeny To Ontogenymentioning
confidence: 99%